The Role of Classroom Management on Mathematics Learning Interest in High School Students - Harapan, Salva Putri; Nazifa, Nur'aini; A At, Hasna Dzakiyya; Husna, Khairuna Nidaul; Maula, Ni'matul (Jurnal Inovasi Pembelajaran Karakter, 2024)
Good classroom management will produce good output for students in their main focus of interest in mathematics. In its application, good school management can include various important aspects, namely, (1) good and effective time management; (2) application of appropriate learning methods; (3) the existence of an interactive relationship between educators and students; and (4) an interactive and pleasant classroom atmosphere. These are some of the factors that can encourage students' interest in learning, especially in mathematics, where the subject is often considered difficult for some students at school. With the writing of this article, it is hoped that it can provide suggestions for teachers to provide variations in determining interesting learning methods so that the material can be well received by students without considering it a burden.